Field guide to the fishes of the Amazon, Orinoco, and Guianas - Sleen, Peter van der; Albert, James S. (Princeton University Press, 2017)
"The Amazon and Orinoco basins in northern South America are home to the highest concentration of freshwater fish species on earth, with more than 3,000 species allotted to 564 genera. Amazonian fishes include piranhas, electric eels, freshwater stingrays, a myriad of beautiful small-bodied tetras and catfishes, and the largest scaled freshwater fish in the world, the pirarucu. Field Guide to the Fishes of the Amazon, Orinoco, and Guianas provides descriptions and identification keys for all the known genera of fishes that inhabit Greater Amazonia, a vast and still mostly remote region of tropical rainforests, seasonally flooded savannas, and meandering lowland rivers. The guide's contributors include more than fifty expert scientists. They summarize the current state of knowledge on the taxonomy, species richness, and ecology of these fish groups, and provide references to relevant literature for species-level identifications. This richly illustrated guide contains 700 detailed drawings, 190 color photos, and 500 distribution maps, which cover all genera. An extensive and illustrated glossary helps readers with the identification keys. The first complete overview of the fish diversity in the Amazon, Orinoco, and Guianas, this comprehensive guide is essential for anyone interested in the freshwater life inhabiting this part of the world."